Combustion behavior and mechanism of Ti-25V-15Cr compared to Ti-6Al-4V alloy. (January 2022) - Shao, Lei; Xie, Guoliang; Liu, Xinhua; Wu, Yuan; Tan, Qing; Xie, Lu; Xin, Shewei; Hao, Fang; Yu, Jiabin; Xue, Wenli; Feng, Kai
Abstract: A distinctive combustion phenomenon is revealed by promoted ignition combustion tests of Ti-25V-15Cr and Ti-6Al-4V alloys. The relationship between ignition temperatures and oxygen pressures obeys the Van't Hoff equation. The ignition temperatures of Ti-25V-15Cr are higher than that of Ti-6Al-4V due to the decomposition and volatilization of V2 O5 . However, the burning velocity of Ti-25V-15Cr is faster than that of Ti-6Al-4V, attributed to the different migration way of solid-liquid interface. The phase structure of the matrix is considered as the key factor that controls the spreading rate of the solid-liquid interface and the burning velocities of Ti-25V-15Cr and Ti-6Al-4V alloys. Graphical Abstract: ga1 Highlights: The burning velocity of Ti-25V-15Cr is faster than that of Ti-6Al-4V. Migration of interface is affected by peritectic reaction for Ti-6Al-4V Migration of interface is controlled by grain boundaries melting for Ti-25V-15Cr. Different ways of interface migration are related to the different phase structures. Ignition temperature depends on alloying elements and burning velocity is affected by phase structure.